Why the Iraqi Resistance to the Coalition Invasion Was So Weak - Hosmer, Stephen T. (RAND Corporation, 2007)
Draws upon information derived primarily from interviews with and interrogations of senior Iraqi military and civilian officials to examine why the Iraqi resistance in March and April 2003 was so weak. It focuses on two questions: (1) Why did the Iraqi Regular Army and Republican Guard forces do so little fighting? and (2) Why did Iraqi leaders fail to adopt certain defensive measures that would have made the Coalition's task more difficult?